Previous exceptions, a critical perspective from the protection of workers' rights - Flores Clavijo, Mónica Cristina (2025)
This article examines Resolution 12-2017 of the National Court of Justice of Ecuador, focusing on its application during the first phase of the single hearing in labor cases. This regulation requires that preliminary exceptions be resolved before proceeding with the analysis of the substance of the case, which poses significant challenges in ensuring effective judicial protection for the safeguarding of labor rights. The research discusses the effectiveness of this resolution in labor matters, identifying conflicts and controversies, and offers recommendations for its improvement. Through a qualitative analysis, it will be concluded that a strict application of the resolution could negatively affect the protection of rights and justice in labor proceedings. The conclusion will suggest adjustments to the regulation to allow for a more comprehensive assessment of the evidence before resolving preliminary exceptions.